2011
DOI: 10.3109/02713683.2011.629069
|View full text |Cite
|
Sign up to set email alerts
|

Early Age-Related Macular Degeneration in Patients with Myocardial Infarction

Abstract: We conclude that the prevalence of early AMD is significantly higher in patients with MI than in a random sample of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“… 6 Epidemiological studies have reported that AMD may be associated with genetics, family history, obesity, low education level, diet, history of cardiovascular and cerebrovascular disease, exposure to sunlight, and various other factors. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Possible associations between AMD and ocular factors such as light iris color, history of previous cataract surgery, short axial length, and hypermetropic refractive error have also been proposed. 15 , 16 However, there are inconsistencies among the literature data, and no studies have been conducted previously in the Turkish population.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Epidemiological studies have reported that AMD may be associated with genetics, family history, obesity, low education level, diet, history of cardiovascular and cerebrovascular disease, exposure to sunlight, and various other factors. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Possible associations between AMD and ocular factors such as light iris color, history of previous cataract surgery, short axial length, and hypermetropic refractive error have also been proposed. 15 , 16 However, there are inconsistencies among the literature data, and no studies have been conducted previously in the Turkish population.…”
Section: Introductionmentioning
confidence: 99%
“…It was established that prevalence of early AMD in the random sample was 7.3%, while in MI patients, it was 54.5% (p < 0.001). AMD increases more with age in females (3.7 and 10.8% at the age 45-54 and 55-64 years, p < 0.05, respectively) while in males, frequency of AMD did not differ significantly between latter age groups (9.9% vs. 11.6%; p > 0.05) [18]. Increased intake of fish reduced the risk of AMD, particularly for two or more servings per week.…”
Section: Risk Factors For Age-related Macular Degeneration Developmentmentioning
confidence: 80%
“…Higher systolic blood pressure, overweight and obesity, and physical exercise duration and frequency are associated with late AMD in women only [17]. The prevalence of AMD is significantly higher in patients with myocardial infarction (MI) than in a simple random sample of the population [18]. It was established that prevalence of early AMD in the random sample was 7.3%, while in MI patients, it was 54.5% (p < 0.001).…”
Section: Risk Factors For Age-related Macular Degeneration Developmentmentioning
confidence: 99%
“…Studies report the associations between CETP rs5882 and HDL‐C levels (Emamian et al, 2015) and Alzheimer‘s disease (Chen, Li, Zou, & Fu, 2014), which share the same pathological pathways as AMD (Xu, Cao, Rajapakse, & Matsubara, 2018). CETP rs708272 was shown to be associated with total cholesterol level changes (Iwanicka et al, 2018), with the risk of coronary atherosclerosis (Wang et al, 2013) and myocardial infarction (Semaev et al., 2019), which are linked to AMD as well (Liutkeviciene et al., 2012). CETP rs3764261 was also associated with serum HDL and APOA1 levels (Huang et al, 2019; Xu, 2019).…”
Section: Methodsmentioning
confidence: 99%